The relationship between policy adjustment of SO2 emissions charge standard and the growth of green total factor productivity—Evidence from China - Liu, Pei; Huang, Wei-Chiao; Chen, Zhongwei; Wang, Shujuan; Ren, Tonglian (Frontiers in Environmental Science, 2022)
Evaluating the impact of environmental pollution charge system reform is necessary to help formulate a suitable policy to achieve a goal of emission control. The paper examines the relationship between policy adjustment of SO2 emissions charge standard (PSC) and urban growth of green total factor productivity (GGTFP) using a natural experiment data of 280 cities in China. The results indicated that the improvement of SO2 emissions charge standard can reduce emission and promote the GGTFP. Furthermore, it reveals an “N” relationship between the policy time period and the GGTFP, and an “Inverted-U” relationship between policy intensity and the GGTFP. The results imply that there is some policy room for policy makers to set a shadow price of pollution charge to maximize policy effect, and it is also important to consider the policy effect in the implementation time and intensity to maximize the policy effect and resource efficiency for the GGTFP and sustainable development.